Handsanitizer from Kitolod Leaf Extract: Optimized Antibacterial Gel Against Staphylococcus aureus with SNI 2588:2017 Quality Analysis - Hisyam Mashadi; Retno Aliyatul Fikroh (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This research aims to test the effectiveness of hand sanitizer based on kitolod leaf extract as a natural alternative for cleaning hands. The research method includes extraction of kitolod leaves, phytochemical testing, making hand sanitizer, antibacterial test, swab test, and analysis based on SNI 2588:2017 standards. Extraction of kitolod leaves using 96% ethanol and phytochemical tests showed the presence of alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids. In the antibacterial test against Staphylococcus aureus, the hand sanitizer formula with 32% kitolod extract showed an inhibition zone of 19.7 ± 0.35 mm. The market hand sanitizer with 70-95% alcohol showed the highest inhibition zone (29.7 ± 5.15 mm). Quality testing of Formula 1 hand sanitizer with SNI 2588:2017 standards, shows that the product meets the established quality requirements. This product has a pH of 6.44 ± 0.45, the expected pH standard to avoid skin irritation. The TPC test results also show that this product's number of bacterial colonies is below the set limit of 2.75x102 ± 5.03 colonies/g, confirming the product's safety as a hand sanitizer.